Study the Effect of Rifampicin in the Level of Thyroid’s Gland Hormones and Thyroid - Stimulating Hormone in Rabbits - Sabrei, D. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The aim of this study was intended to study the effect of rifampicin in the level of thyroid’s gland hormones (T4 ØŒT3) and thyroid -stimulating hormone (TSH) in rabbits. Eight male rabbits were used through out this study, their weights were measured before the starting of the experiment. Animals were divided into two groups (each group contains 4 rabbits), the first group was administrated daily with 15 mg/Kg physiological normal saline for 35 days and used as a control group, while the second group was administrated with 15 mg /Kg daily for 35 day of rifampicin capsule 300 mg. At the end of the experiment, all of animal groups were weighted and the sera was prepared to measure the hormones. The results showed that there was a significant decrease (P < 0.05) in the mean of animals weights in the second group that was treated with rifampicin in comparison with the control group. A significant increase (P < 0.05)was in T4, and T3 hormones level, and a significant decrease (P < 0.05)was in TSH hormone level in the second group that treated with rifampicin in comparison with the control group. From this study, can conclude that rifampicin has a negative effect on thyroid gland function which might disorder on the secretion activity of thyroid gland hormones.